Community Service Through Family Parenting Socialization to Increase Children's Learning Motivation in Karangtumaritis Village - Ahmad Hadin Assyarif; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Socialization is one of the means that greatly influences a person's personality. Socialization is also commonly referred to as role theory. Because in the process of socialization, the roles that must be played by each individual are taught. Parenting or the process of educating children today (parenting patterns) is very important, therefore parenting must be instilled early on by some parents to their children. Because after all, this parenting pattern has a very important role for children and for the future of children. Parenting itself means the way or pattern of parenting parents to their children to shape the personality of the child, and at the same time to know the interests and talents of children as early as possible so that parents can adjust to the level of education that suits their child's wishes. Good parenting is one powerful way to find out a child's character. This activity is one of the devotion of knowledge that I can do in the series of KKN PPM processes. Carrying out activities that can benefit children and socializing how parents can best raise children in Karangtumaritis Village, this activity is the main goal in every program we implement. The Community Service Activity of Real Work Lecture in Karangtumaritis Village took place in July 2024 - August 2024 with the theme of parenting and stunting. This study uses the pretest-posttest method which is a type of quasi-experimental research. This study tests initial knowledge before being given an intervention or material, namely in the form of a pretest and after the intervention was given, a posttest was given. The purpose of this study was to determine the level of knowledge of participants before and after the intervention and to find out more accurate results related to the effectiveness of the success of the counseling. This study uses a health promotion intervention, namely a lecture method using power point media and questions and answers. Health promotion includes material related to parenting patterns to increase children's learning motivation with a duration of 1 x 30 minutes with 1 presentation. The success of this program is seen in terms of the responsiveness of PKK mothers and also the understanding of the material about the importance of good parenting. Many parents are enthusiastic and concerned after being educated about parenting materials, the implementation of the materials is then practiced by distributing questionnaires to parents who are able to practice and train souls with noble morals.